2022
DOI: 10.3390/ijms23105841
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fluorescence Imaging of Native Proteins Using a Fluorescent Probe with a Cell-Membrane-Permeable Carboxyl Group

Abstract: Although various methods for selective protein tagging have been established, their ap plications are limited by the low fluorescent tagging efficiency of specific terminal regions of the native proteins of interest (NPIs). In this study, the highly sensitive fluorescence imaging of single NPIs was demonstrated using a eukaryotic translation mechanism involving a free carboxyl group of a cell-permeable fluorescent dye. In living cells, the carboxyl group of cell-permeable fluorescent dyes reacted with the lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Additionally, expression of Tat protein tagged with AVI peptidewas observed in both HeLa cells and cell‐free extracts to confirm translational activity. [ 41 ] The designed C‐terminal biotinylated fluorescent Tat consisted of the N‐terminal fluorophore 5‐FAM (Ex/Em: 492/512 nm) conjugated to the three different complex forms mentioned above. Fluo imaging of HeLa cell extracts demonstrated that PFM‐tRNAi Met complex showed the highest fluorescent Tat expression (Figure 3C), and the NPFM‐tRNAi Met complex showed the lowest (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, expression of Tat protein tagged with AVI peptidewas observed in both HeLa cells and cell‐free extracts to confirm translational activity. [ 41 ] The designed C‐terminal biotinylated fluorescent Tat consisted of the N‐terminal fluorophore 5‐FAM (Ex/Em: 492/512 nm) conjugated to the three different complex forms mentioned above. Fluo imaging of HeLa cell extracts demonstrated that PFM‐tRNAi Met complex showed the highest fluorescent Tat expression (Figure 3C), and the NPFM‐tRNAi Met complex showed the lowest (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Biotinylated Cy5-Tat-EGFP was detected by binding to Neu-trAvidin beads, using HeLa cell extracts prepared without washing to preserve endogenous components. As previously reported, [32,41] a plasmid expressing the C-terminal fragment of Tat with AVI-tag and His-tag was prepared(Figure 4C and Figure S6). His-tag facilitated GFP binding and Ni-NTA bead based analysis, as confirmed by fluo microscopy.…”
Section: Validation Of Non-denatured Fluorescent Tat Expression Using...mentioning
confidence: 99%
See 2 more Smart Citations
“…Bioorthogonal labeling schemes that rely on the incorporation of minimal tag bioorthogonalized building blocks and suitably functionalized probes allow minimal linkage error, and very importantly, these are not limited to proteins [ 37 – 39 ]. Synthetically tailored organic fluorophores offer much smaller size and allow greater flexibility in terms of the site specificity of labeling, often providing improved photophysical properties such as a wider spectral range and greater photostability or brightness compared with, e.g., FPs [ 2 , 33 ]. Furthermore, tailored synthetic probes may also address challenges such as auto- and background fluorescence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%